Evaluating complete silage for goat feeding in Gorontalo, Indonesia - Sayuti, Muh.; Syahrudin; Sahara, Laode; Rachman, Agus Bahar; Metaragakusuma, Andi Patiware; Febrisiantosa, Andi Febrisiantosa (Institut Teknologi Bandung, 2024)
Forage shortages and inconsistent quality in developing countries pose significant challenges to the small ruminant sector. Feeding ruminants with conserved forages is crucial to address this issue and ensure successful ruminant management in developing countries. The use of sorghum crops mixed with grasses as fermentation feed has gained thought because of its high protein efficiency, relatively high digestible energy, and total digestible nutrients. Therefore, this study aimed to determine feed intake, nutrient digestibility, and growth performance in Gorontalo local goats fed complete silage with varying levels of mixed concentrations of sorghum straw with grasses. Sixteen male Gorontalo local goats were preferred from the local area and randomly divided into four groups using a completely randomized design (CRD). Over 84 days, four different complete silage diets (T1, T2, T3, and T4) were given to goats. The goats' daily nutrient intake, digestibility, and growth performance were analyzed. The T1 diet consisted of 30% grass and 60% sorghum straw, the T2 diet included 20% grass and 70% sorghum straw, the T3 diet contained 10% grass and 60% sorghum straw, and the T4 diet had no grass and 90% sorghum straw. The study found that the dry matter intake (DMI) of goats ranged from 330.2 to 335.1 g/day, approximately 3% of their body weight. The digestibility values of dry matter, crude protein, crude fat, neutral detergent fiber, acid detergent fiber, and energy decreased as the amount of sorghum straw in the silage rations increased. The average daily gain (ADG) (gr/day) in T1, T2, T3, and T4 was affected, with T1 showing the highest ADG (43.2) and T4 showing the lowest (40.3). The Feed Conversion Ratio (FCR) value was also influenced, with T1 and T2 showing the best FCR (7.8 and 7.7) and T3 showing the worst (8.2). Based on these findings, it is recommended to limit the amount of sorghum straw to 60%-70% in complete silage for local goats in Gorontalo, especially in tropical areas where goats are common and sorghum is readily available.